Can the Release of a Monetary Overhang Trigger Hyperinflation? - Osband, Kent (IMF Working Papers; Working Paper ;, 1992)
It is widely feared that, once prices are decontrolled in the formerly centrally-planned economies, households' release of previously accumulated money will trigger a hyperinflation. This paper finds, instead, that whether a country's fiscal, monetary, and labor market policies are destabilizing typically does not depend on the money stock. However, the release of a monetary overhang can precipitate a large initial real wage shock. To the extent such a shock is not feasible politically, there is a motive for monetary reform, which must be weighed against the cost of reduced public confidence in money.